Impact of Technical Condition of Tires (Motorcycles) on Passenger Safety - Borhanudin, Siti Nur Nazurah; Rahmah Mahmudin (Progress in Engineering Application and Technology, 2024)
Motorcycles are a ubiquitous mode of transportation in Malaysia, with millions of riders navigating the country's roads daily. Despite their convenience and flexibility, motorcycles are also prone to accidents, which can have far-reaching consequences for both riders and pedestrians. The safety, performance, and efficiency of a motorcycle are heavily dependent on its tire components, which play a critical role in maintaining traction, stability, and control on the road. The primary objective of this research project is to investigate the impact of tire pressure on fuel consumption in motorcycles. To achieve this goal, a Honda Wave Alpha motorcycle was employed as the test vehicle, with experiments conducted at various tire pressure conditions: normal inflation, under-inflation, and over-inflation. The experiment was conducted at the Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh campus, with a goal distance of 19 km under dry conditions. The results indicated that normal tire pressure conditions yielded the best fuel efficiency, with a consumption rate of 450 milliliters per 19 Km, while under-inflation and over-inflation led to increased fuel consumption by 5.18% and 7.40%, respectively. By examining the relationship between tire pressure and fuel consumption, as well as investigating the attitudes and behaviors of motorcycle riders towards tire maintenance, this research provides valuable insights that can inform strategies for improving road safety and reducing the risk of accidents involving motorcycles in Malaysia.